THE DEVELOPMENT OF SCIENCE LEARNING DEVICE BASED ON SCIENCE EDUTAINMENT TO IMPROVE STUDENT'S LEARNING MOTIVATION AND COGNITIVE LEARNING ACHIEVEMENT - Tiffani Anggarniastiti; Dadan Rosana; Wita Setianingsih (Journal of Science Education Research, 2017)
The aims of this research are 1) to produce science learning device based on Science Series which is feasible according to the validators, 2) to know the students ' response to Science Edutainment learning, 3) to know the improvement of students ' learning motivation after using learning device which developed, 4) to know the improvement of students ' cognitive learning achievement after using learning device which was developed. This research is categorized as RnD research with 4 d model (Define, Design, Develop, and Disseminate). Instruments which were used in this research are validation forms of learning device, students ' questionnaire response to Science Education learning, students ' questionnaire of learning motivation, pretest and posttest, and learning task observation form. The data analysis techniques used in this research are qualitative and quantitative. The results of this research are: 1) it has been produced science learning device based on Science Series which is feasible with excellent category (A) according to the validators, 2) science learning which used learning devices based on Science Edutainment get students ' response with good category (B), 3) science learning device can improve students ' learning motivation with percentage 10.74%, 4) science learning device can improve students ' cognitive learning achievement with result of gain score is 0.73 and categorized as high category.